2019
DOI: 10.1101/623934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct monitoring of cAMP at the cardiac ryanodine receptor using a novel targeted fluorescence biosensor mouse

Abstract: Rationale-Cyclic adenosine monophosphate (cAMP) is a ubiquitous second messenger which, upon b-adrenergic receptor (b-AR) stimulation, acts in microdomains to regulate cardiac excitation-contraction coupling by activating the cAMP-dependent protein kinase (PKA) phosphorylation of calcium handling proteins. One crucial microdomain is in vicinity of the cardiac ryanodine receptor type 2 (RyR2) which is associated with arrhythmogenic diastolic calcium leak from the sarcoplasmic reticulum (SR) often occurring upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(34 reference statements)
2
4
0
Order By: Relevance
“…These b 1 -AR-cAMP pools were regulated predominately via PDE4 followed by a smaller contribution by PDE3, with little to no PDE2 regulation. Interestingly, these PDE4 effects in the RyR microdomain were two-to threefold greater than that in the cytosol, consistent with past evidence that PDE4 regulates cAMP dynamics within the RyR microdomain [107].…”
Section: Ryr Microdomains In the Healthy Heartsupporting
confidence: 88%
See 1 more Smart Citation
“…These b 1 -AR-cAMP pools were regulated predominately via PDE4 followed by a smaller contribution by PDE3, with little to no PDE2 regulation. Interestingly, these PDE4 effects in the RyR microdomain were two-to threefold greater than that in the cytosol, consistent with past evidence that PDE4 regulates cAMP dynamics within the RyR microdomain [107].…”
Section: Ryr Microdomains In the Healthy Heartsupporting
confidence: 88%
“…However, in mouse cardiomyocytes both PDE3 and PDE4 have been shown to be required to maintain basal cAMP‐PKA signalling within the RyR2 microdomain [108]. Furthermore, while FRET studies using Epac1‐JNC biosensor revealed PDE4 to be the main PDE family responsible for regulating isoproterenol‐induced cAMP pools within the RyR microdomain, PDE3 inhibition was also able to increase cAMP levels at the RyR microdomain [107].…”
Section: Ryr Microdomains In Hfrefmentioning
confidence: 99%
“…Epac1-camp sensor was modified to study cAMP dynamics in the vicinity of cardiac ryanodine receptors type 2 (RyR2) [ 61 ]. The cytoplasmic N-terminus of junction (JNC) was fused to the sensor.…”
Section: Fluorescence-based Camp Sensorsmentioning
confidence: 99%
“…To gain further insight into microdomains around calcium handling proteins, our group has developed new versions of the cAMP biosensor Epac1-camps that are localized either to caveolin-rich plasma membrane (Perera et al, 2015) or to major SR membrane proteins SERCA2a and RyR, by fusing the sensor to PLN (Sprenger et al, 2015) or junctin (Berisha et al, 2019), respectively (see Figure 1). These sensors have been expressed in ventricular myocytes of transgenic mice to allow the imaging of cAMP in both normal and disease states.…”
Section: Visualizing Local Cyclicamp In the Vicinity Of Ion Channels mentioning
confidence: 99%
“…In experiments using myocytes isolated from mice subjected to pressure overload to induce cardiac hypertrophy and early heart failure, these biosensors uncovered a disease driven intracellular redistribution of several PDE families. For example, PDE2 was shown to switch locations between β 1 - and β 2 -AR-associated plasma membrane microdomains (Perera et al, 2015), while PDE3A switched isoforms from A2 and A1 and relocated from the sarcolemma to the SR (Perera et al, 2015; Berisha et al, 2019). This type of PDE redistribution had a functional impact on myocyte contractility, enhancing β 1 -AR mediated inotropic increases in contractile force, especially when natriuretic peptide receptors were co-stimulated (Perera et al, 2015).…”
Section: Visualizing Local Cyclicamp In the Vicinity Of Ion Channels mentioning
confidence: 99%